Pengaruh Social Support Rekan Kerja dan Interpersonal Communication terhadap Job Satisfaction Karyawan Dot Max Coffee and Eatery di Kota Madiun - Vania Eka Puspita; Sonja Andarini (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the influence of coworker social support and interpersonal communication on job satisfaction among employees at Dot Max Coffee and Eatery in Madiun City. This study employs a quantitative method, using a questionnaire distributed to employees as respondents for data collection. The data obtained were then analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that coworker social support and interpersonal communication fall into the “good” category based on respondents’ perceptions. Partially, coworker social support has a positive and significant effect on employee job satisfaction. Similarly, interpersonal communication also has a positive and significant effect on job satisfaction. Simultaneously, both variables were found to have a positive and significant effect on the job satisfaction of employees at Dot Max Coffee and Eatery in Madiun City. Furthermore, the results indicate that the model used has excellent explanatory power regarding variations in employee job satisfaction. This suggests that coworker support and interpersonal communication are key factors that can enhance job satisfaction. The stronger the social relationships and communication within the workplace, the higher the level of employee job satisfaction.